Super-hydrophobic antibacterial fabric with photothermal effect and preparation method
By constructing the porous structure of photothermal preparations and hydrophobic silica nanoparticles in superhydrophobic antibacterial fabrics, combined with low surface energy silane coupling agents, the problems of low antibacterial efficiency and short antibacterial life in the prior art are solved, and high-efficiency and long-term antibacterial effect and superhydrophobic high-temperature resistance are achieved.
Patent Information
- Application Number
- CN202510047210.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing superhydrophobic antibacterial fabrics have problems such as low antibacterial efficiency and short antibacterial life of active sterilization materials. In addition, the combination of superhydrophobic properties and sterilization properties is poor, making it difficult to maintain efficient antibacterial effects for a long time.
The porous structure is constructed using photothermal preparations and hydrophobic silica nanoparticles, combined with low-surface energy silane coupling agent, and superhydrophobic antibacterial fabrics with photothermal effects are prepared through repeated immersion and heat crosslinking processes.
The superhydrophobicity, heat resistance and high-efficiency antibacterial effect of the fabric are achieved, with an antibacterial rate of up to 99.0%, a wide antibacterial range, a long antibacterial life, and no drug resistance.
Smart Images

Figure CN119754022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of super-hydrophobic antibacterial fabrics, and in particular to a super-hydrophobic antibacterial fabric with photothermal effect and a preparation method thereof. Background Art
[0002] Health protection textiles have made important contributions to preventing virus transmission, reducing cross infection, and improving the success rate of surgery, such as respiratory masks, protective clothing, and medical textiles. However, most textiles are hydrophilic, and bacteria can easily grow and multiply on their surfaces. The biofilm formed poses a serious threat to personal health and public health. Therefore, it is particularly urgent to study the antibacterial properties of textiles.
[0003] At present, the antibacterial strategy of textiles mainly includes the construction of super-hydrophobic surfaces and the introduction of bactericidal materials. Super-hydrophobic surfaces use their micro-nano rough structure and extremely low surface energy to capture air in water, effectively reducing the adhesion between bacteria and the surface, thereby reducing the probability of biofilm formation; while bactericidal materials exert their active bactericidal properties by contacting bacteria or releasing bactericides, inactivating bacteria attached to the surface or free in the surrounding environment.
[0004] However, the antibacterial fabrics prepared by these two antibacterial strategies have shortcomings. The structural defects of the superhydrophobic surface and its interaction with microorganisms make it difficult for the captured air layer to remain stable for a long time, resulting in a small number of bacteria breaking through the physical barrier and attaching to the surface; and the bactericidal material has a greatly reduced bactericidal efficiency and service life due to the dead bacteria covering the surface. Therefore, it is of great significance to combine the superhydrophobic and bactericidal properties of textiles.
[0005] In order to achieve a long-term and efficient antibacterial effect, the Chinese invention patent with the announcement number CN116219763B discloses that a secondary amine hydrophobic antibacterial modifier containing a (poly)dopamine structure is prepared by reacting a natural organic antibacterial agent phenolic ketone compound with dopamine under acidic conditions, and then reacting it with cellulose fabric under aerobic alkaline conditions to obtain a super-hydrophobic cellulose fabric with an inhibition rate greater than 99.0%; in addition, the Chinese invention patent application with the announcement number CN115928441B discloses that a hydrophobic cotton fabric with a contact angle greater than 135° and an antibacterial rate of up to 100% is formed by the oxidation self-polymerization of dopamine, the Schiff base reaction of hexadecylamine and polydopamine, and the loading of the antibacterial agent triclosan. However, the above materials are all added with organic antibacterial agents. Although the bactericidal effect is good and the bactericidal speed is fast, it is easy to make bacteria resistant, and the heat resistance and stability are poor.
[0006] In addition, the superhydrophobic properties of the above materials still need to be improved. Studies have found that the self-cleaning effect of superhydrophobic surfaces can be used to remove attached dead bacteria and reduce their adhesion on the surface of antibacterial materials, which plays a key role in extending the service life of antibacterial materials. Summary of the invention
[0007] In view of the problems existing in the prior art such as low antibacterial efficiency of passive super-hydrophobic antibacterial adhesion materials and short antibacterial life of active bactericidal materials, the purpose of the present invention is to provide a method for preparing a super-hydrophobic antibacterial fabric with a photothermal effect. The process is simple, and the super-hydrophobic antibacterial fabric has excellent photothermal cycle stability and super-hydrophobic high temperature resistance, and can maintain high antibacterial efficiency for a long time and has high safety.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a super-hydrophobic antibacterial fabric with photothermal effect, comprising the following steps:
[0009] Step S1, surface treating the front and back sides of the fabric with oxygen plasma respectively, then immersing the fabric in a photothermal preparation aqueous dispersion with a volume concentration of 3 to 10 mg / mL for 1 to 3 minutes, then taking the fabric out and drying it in an oven at 60 to 100° C., repeating the immersion and drying 2 to 5 times to obtain a photothermal fabric;
[0010] Step S2, adding a mixture of 0.5-2 parts of ammonia water and 2-6 parts of water to 95 parts of ethanol by volume, mixing evenly, then adding 0.5-3g of a silane coupling agent with an alkane chain, stirring for 4-12h at a temperature of 25-60°C to obtain a hydrolysis solution, then adding 0.075-0.9g of hydrophobic silica nanoparticles to the hydrolysis solution, and subjecting the solution to ultrasonic treatment for 5-15min to obtain a uniformly dispersed stable modified dispersion;
[0011] Step S3, placing the photothermal fabric treated in step S1 into the modified dispersion prepared in step S2, stirring at room temperature for 5 to 10 minutes, taking out the photothermal fabric and placing it in an oven at 80 to 120° C. for curing for 0.5 to 4 hours, to obtain a super-hydrophobic antibacterial fabric with a photothermal effect, wherein a silane coupling agent / hydrophobic silica nanoparticle composite coating is attached to the surface of the fabric base of the super-hydrophobic antibacterial fabric, wherein the hydrolyzed silane coupling agent with an alkane chain partially undergoes self-degradation under high temperature conditions of 80 to 120° C. Condensation occurs partially with the hydroxyl or carboxyl groups of the photothermal agent, and partially with the hydroxyl groups between fibers through electrostatic or hydrogen bonding, so that the silane coupling agent / hydrophobic silica nanoparticle composite coating, the fabric base of the superhydrophobic antibacterial fabric and the photothermal agent layer all have good adhesion, and the photothermal agent and hydrophobic nano-silica in the photothermal agent aqueous dispersion are densely accumulated on the fiber surface of the superhydrophobic antibacterial fabric, forming an undulating porous structure formed by a large number of nano-papillae, constructing a uniform micro-nano rough structure.
[0012] The present invention loads the photothermal preparation on the surface of the fabric by repeated immersion-drying, and then applies a mixed solution of hydrophobic silica nanoparticles and a silane coupling agent with an alkane chain to the fabric under alkaline conditions, and obtains a super-hydrophobic antibacterial fabric with a photothermal effect after thermal crosslinking. The photothermal preparation and the hydrophobic nano-silica synergistically construct a uniform micro-nano rough structure on the surface of the fabric, and the silane coupling agent with an alkane chain undergoes a condensation reaction with the hydroxyl or carboxyl group of the photothermal preparation after hydrolysis under alkaline conditions and is grafted on the surface of the photothermal preparation layer, thereby giving the fabric a low surface energy. The rough morphology is combined with a special chemical structure to achieve super-hydrophobicity on the fabric surface. In addition, the introduction of the photothermal preparation gives the fabric excellent photothermal conversion performance. Under the passive anti-bacterial adhesion of the super-hydrophobic surface and the active bactericidal action of the photothermal preparation, the fabric shows excellent antibacterial efficiency against a variety of bacteria, and the self-cleaning effect of the super-hydrophobic surface can remove attached dead bacteria to reduce adhesion and extend the service life of the antibacterial material. The preparation process provided by the present invention is simple and low-cost, and the prepared photothermal super-hydrophobic antibacterial fabric has excellent stability, a wide antibacterial range, high safety and no drug resistance.
[0013] In a further technical solution, in step S1, hydrogen bonds or electrostatic interactions between the hydroxyl and carboxyl groups of the photothermal preparation and the fabric fibers cause the fiber surface of the fabric to become rough after immersion treatment, thereby increasing the physical adhesion between the photothermal preparation and the fiber surface of the fabric and giving the fabric photothermal properties.
[0014] In a further technical solution, in step S1, the photothermal agent aqueous dispersion is a solution obtained by putting the photothermal agent into water and dispersing it evenly through ultrasonic treatment, and the photothermal agent is selected from any one of MXene, carboxylated carbon tubes, and carboxylated carbon black.
[0015] In a further technical solution, in step S1, the material of the fabric is any one of polypropylene, polyethylene, polyester, polyurethane and cellulose; the type of the fabric is meltblown fabric, non-woven fabric or woven fabric.
[0016] In a further technical solution, in step S2, the silane coupling agent with an alkane chain undergoes a hydrolysis reaction in ethanol under the promotion of the ammonia water and the water, and the obtained hydrolysis reactant has good compatibility with the hydrophobic silica nanoparticles. After the ultrasonic treatment, the hydrolysis reactant and the hydrophobic silica nanoparticles are uniformly dispersed in the solution and maintain the stable modified dispersion.
[0017] In a further technical solution, in step S2, the silane coupling agent with an alkane chain is selected from at least one of dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane and octadecyltriethoxysilane.
[0018] In a further technical solution, in step S2, the mass concentration of the silane coupling agent with an alkane chain in the solvent consisting of ethanol, ammonia water and water is 5 to 30 mg / mL.
[0019] In a further technical solution, in step S2, the particle size of the hydrophobic silica nanoparticles is 20 to 80 nm; and the mass ratio of the hydrophobic silica nanoparticles to the silane coupling agent with an alkane chain is 15 to 30 wt%.
[0020] A super-hydrophobic antibacterial fabric with photothermal effect is prepared by the above-mentioned method for preparing a super-hydrophobic antibacterial fabric with photothermal effect. The super-hydrophobic antibacterial fabric with photothermal effect combines passive super-hydrophobic antibacterial adhesion and active photothermal sterilization in antibacterial applications, with an antibacterial rate of more than 99.0%, a wide antibacterial range and a long antibacterial life.
[0021] The advantages of the present invention compared with the prior art are:
[0022] 1. The process of the present invention is simple, and the process is suitable for mass production, the comprehensive production cost is low, the super-hydrophobic antibacterial fabric has excellent light-heat cycle stability and super-hydrophobic high temperature resistance, and can maintain high antibacterial efficiency for a long time, and has high safety. The raw material cost required for implementing the preparation method of the present invention is low, and the super-hydrophobic antibacterial fabric of the present invention has the advantages of low energy consumption, environmental friendliness and high safety, and shows great value in medical protective materials.
[0023] 2. The present invention constructs a fabric with excellent super-hydrophobicity through a porous rough structure formed by dense accumulation of nano-papillaries constructed by photothermal preparations and hydrophobic nano-silica and a binary synergistic effect of a low surface energy silane coupling agent; at the same time, a dehydration condensation reaction occurs between the photothermal preparation and the silane coupling agent to form a chemical cross-linked structure. In addition, the present invention introduces a photothermal preparation layer to allow the fabric to heat up rapidly under sunlight or near-infrared light, and the surface temperature can reach 120°C. Due to the structural stability, the fabric shows excellent photothermal cycle stability, that is, the super-hydrophobic antibacterial fabric of the present invention can maintain super-hydrophobicity for a long time at a high temperature of 120°C, effectively improving the heat resistance stability and antibacterial life of the fabric.
[0024] 3. The present invention first loads a photothermal agent on the surface of the fabric to impart photothermal properties, and then introduces a composite coating formed by hydrophobic silica nanoparticles and a silane coupling agent with an alkane chain to reduce the surface energy of the material and construct a micro-nano rough structure to prepare an antibacterial fabric with excellent photothermal and super-hydrophobic properties; the super-hydrophobic antibacterial fabric prepared by the present invention has a fabric surface water contact angle of 158°, and a surface temperature of 120°C under near-infrared light irradiation, showing excellent photothermal cycle stability and super-hydrophobic high temperature resistance. The antibacterial rate of the super-hydrophobic antibacterial fabric exceeds 99.0% under the synergistic effect of passive super-hydrophobic antibacterial adhesion and active photothermal sterilization.
[0025] 4. The super-hydrophobic antibacterial fabric of the present invention is prepared by the above-mentioned preparation method. The super-hydrophobic antibacterial fabric of the present invention realizes the integrated application of super-hydrophobic antibacterial and photothermal sterilization, and exhibits excellent antibacterial effect. On the one hand, the super-hydrophobicity of the fabric greatly reduces the adhesion of bacteria on the surface of the material. On the other hand, the photothermal preparation layer quickly kills a small amount of bacteria attached to the surface of the material under light conditions, thereby realizing double protection. The fabric has high antibacterial efficiency, a wide antibacterial range, a long antibacterial life, and is safe, reliable, and has no drug resistance. The photothermal super-hydrophobic fabric can combine passive super-hydrophobic antibacterial adhesion and active photothermal sterilization in antibacterial applications. The antibacterial rate is as high as 99.0% or more, the antibacterial range is wide, and the antibacterial life is long. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Scanning electron microscope images of the superhydrophobic antibacterial fabric with photothermal effect prepared in Example 1 (magnifications: 700 times, 5000 times and 50000 times).
[0027] Figure 2 The surface temperature of the super-hydrophobic antibacterial fabric with photothermal effect prepared in Example 1 changes with the near-infrared light irradiation time.
[0028] Figure 3 The resistance effects of the original fabric and the superhydrophobic antibacterial fabric with photothermal effect prepared in Example 1 against Escherichia coli and Staphylococcus aureus before and after near-infrared light irradiation. DETAILED DESCRIPTION
[0029] Example 1
[0030] First, the front and back sides of the cotton fabric were treated with oxygen plasma for 1 min respectively, then immersed in a 4 mg / mL MXene nanosheet aqueous dispersion for 2 min, taken out and dried in a 60°C oven, and the immersion-drying process was repeated 4 times; then, a mixture of 1 mL of ammonia water and 4 mL of water was added to 95 mL of ethanol, mixed evenly, and then 2 g of hexadecyltrimethoxysilane was added, stirred at 25°C for 12 h, and then 0.4 g of hydrophobic nano-silica with a particle size distribution of 20 to 40 nm was added to the solution. After ultrasonic dispersion treatment for 5 min, a uniformly dispersed modified dispersion was obtained; finally, the photothermal fabric loaded with MXene nanosheets was placed in the modified dispersion prepared above, stirred at room temperature for 10 min, taken out and placed in an oven at 100°C for curing for 1 h to obtain a superhydrophobic antibacterial fabric with photothermal effect.
[0031] Figure 1 This is a scanning electron microscope image of the photothermal superhydrophobic antibacterial fabric prepared in Example 1. It can be seen that the hydrophobic nano-silica particles are evenly coated on the surface of the fabric, accumulating to form a large number of nano-papillae, which together with the fabric fibers construct a micro-nano rough structure, and the fabric achieves super-hydrophobic properties with a surface contact angle of 152°. In addition, due to the stable cross-linked structure formed between hexadecyltrimethoxysilane and MXene nanosheets, the fabric exhibits excellent heat resistance, and it still maintains super-hydrophobicity after being treated in a 120°C environment for 72 hours, with a contact angle of 150°.
[0032] Figure 2 The surface temperature of the photothermal superhydrophobic antibacterial fabric prepared in Example 1 changes with the near-infrared light irradiation time. It can be seen that the fabric heats up rapidly within 1 minute of irradiation, and the surface temperature rises to 110°C after 1 minute, and then slowly heats up, and the surface temperature rises to 114°C after 5 minutes. This shows that MXene nanosheets can effectively absorb and capture light under near-infrared light irradiation, and convert light into heat, which is quickly transferred to the fabric through the high thermal conductivity MXene.
[0033] Figure 3The photothermal super-hydrophobic antibacterial fabric prepared in Example 1 shows its resistance to Escherichia coli and Staphylococcus aureus before and after near-infrared light irradiation. It can be seen that the bacterial colonies cultured on the original fabric as the substrate are densely distributed on the agar plate; and the photothermal super-hydrophobic antibacterial fabric prepared in this embodiment is difficult for bacteria to adhere to the sample surface due to its special wettability, thereby greatly reducing the bacterial content on the agar plate. However, since the rough structure of the super-hydrophobic surface is inevitably damaged during storage, some colonies still exist on the surface of the fabric; in addition, the photothermal super-hydrophobic antibacterial fabric is irradiated with near-infrared light for 10 minutes, and the MXene layer quickly absorbs heat and heats up, inactivating the surface bacteria, and the anti-adhesion effect of the super-hydrophobic surface causes the attached dead bacteria to peel off, so there is no colony growth on the agar plate, and the antibacterial rate against Escherichia coli and Staphylococcus aureus is as high as 100%.
[0034] The test results of the hydrophobicity, high temperature stability and photothermal conversion performance of the fabric are shown in Table 1, and the test results of the antibacterial performance of the fabric are shown in Table 2.
[0035] Example 2
[0036] First, the front and back sides of the polypropylene meltblown cloth were treated with oxygen plasma for 1 min respectively, and then immersed in a 3 mg / mL carboxylated carbon nanotube aqueous dispersion for 1 min, taken out and dried in an oven at 100°C, and the immersion-drying process was repeated 5 times; then, a mixture of 0.5 mL of ammonia water and 6 mL of water was added to 95 mL of ethanol, mixed evenly, and then 0.5 g of dodecyltrimethoxysilane was added, stirred at 40°C for 8 h, and then 0.15 g of hydrophobic nano-silica with a particle size of about 80 nm was added to the solution, and a uniformly dispersed modified dispersion was obtained after ultrasonic dispersion treatment for 15 min; finally, the photothermal fabric loaded with carboxylated nanotubes was placed in the modified dispersion prepared above, stirred at room temperature for 5 min, taken out and placed in an oven at 80°C for curing for 4 h to obtain a superhydrophobic antibacterial fabric with photothermal effect.
[0037] The test results of the hydrophobicity, high temperature stability and photothermal conversion performance of the fabric are shown in Table 1, and the test results of the antibacterial performance of the fabric are shown in Table 2.
[0038] Example 3
[0039] First, the front and back sides of the polyurethane non-woven fabric were treated with oxygen plasma for 1 min respectively, and then immersed in a 10 mg / mL carboxylated carbon black aqueous dispersion for 3 min, taken out and dried in an oven at 80°C, and the immersion-drying process was repeated twice; then, a mixture of 2 mL of ammonia water and 2 mL of water was added to 95 mL of ethanol, mixed evenly, and then 3 g of octadecyltriethoxysilane was added, stirred at 60°C for 4 h, and then 0.45 g of hydrophobic nano-silica with a particle size distribution of 30 to 50 nm was added to the solution, and a uniformly dispersed modified dispersion was obtained after ultrasonic dispersion treatment for 10 min; finally, the photothermal fabric loaded with carboxylated carbon black was placed in the modified dispersion prepared above, stirred at room temperature for 8 min, taken out and placed in an oven at 120°C for curing for 0.5 h, to obtain a superhydrophobic antibacterial fabric with photothermal effect.
[0040] The test results of the hydrophobicity, high temperature stability and photothermal conversion performance of the fabric are shown in Table 1, and the test results of the antibacterial performance of the fabric are shown in Table 2.
[0041] Example 4
[0042] First, the front and back sides of the polyester fabric were treated with oxygen plasma for 1 min respectively, and then immersed in a 6 mg / mL MXene nanosheet aqueous dispersion for 2 min, taken out and dried in an oven at 80°C, and the immersion-drying process was repeated 3 times; then, a mixture of 2 mL of ammonia water and 4 mL of water was added to 95 mL of ethanol, mixed evenly, and then 2.5 g of hexadecyltriethoxysilane was added, stirred at 60°C for 6 h, and then 0.6 g of hydrophobic nano-silica with a particle size distribution of 20 to 60 nm was added to the solution. After ultrasonic dispersion treatment for 10 min, a uniformly dispersed modified dispersion was obtained; finally, the photothermal fabric loaded with MXene nanosheets was placed in the modified dispersion prepared above, stirred at room temperature for 5 min, taken out and placed in an oven at 90°C for curing for 2 h to obtain a superhydrophobic antibacterial fabric with photothermal effect.
[0043] The test results of the hydrophobicity, high temperature stability and photothermal conversion performance of the fabric are shown in Table 1, and the test results of the antibacterial performance of the fabric are shown in Table 2.
[0044] Comparative Example
[0045] In order to verify the key role of the rough structure in the photothermal superhydrophobic antibacterial fabric prepared by the present invention in achieving superhydrophobic performance, and to verify the significance of the superhydrophobic surface in improving the antibacterial efficiency, a comparison was made with a fabric prepared without adding hydrophobic silica nanoparticles.
[0046] First, the front and back sides of the cotton fabric were treated with oxygen plasma for 1 min respectively, and then immersed in a 4 mg / mL MXene nanosheet aqueous dispersion for 2 min. After being taken out, it was placed in an oven at 60°C for drying, and the soaking-drying process was repeated 4 times. Subsequently, a mixture of 1 mL of ammonia water and 4 mL of water was added to 95 mL of ethanol. After mixing evenly, 2 g of hexadecyltrimethoxysilane was added, and stirred at 25°C for 12 h. Finally, the photothermal fabric loaded with MXene nanosheets was placed in the above-prepared dispersion, stirred at room temperature for 10 min, taken out, and placed in an oven at 100°C for curing for 1 h to obtain a superhydrophobic antibacterial fabric with photothermal effect.
[0047] The test results of the hydrophobicity and photothermal conversion performance of the fabric are shown in Table 1, and the test results of the antibacterial performance of the fabric are shown in Table 2.
[0048] Performance Testing
[0049] (1) Scanning electron microscope test
[0050] The morphology was observed using a scanning electron microscope (Zeiss sigma300, Germany) with an accelerating voltage of 5 kV. Before testing, the fabric was fixed on the sample table with conductive glue and gold-sprayed.
[0051] (2) Contact angle test
[0052] The contact angle of water droplets on the coating surface was tested using a contact angle meter (SDC-200S, Dongguan Shengding Precision Instrument Co., Ltd.). The water droplet size was 5 μL, and the contact angle value was calculated as the average value at 5 locations on the fabric surface.
[0053] (3) Photothermal conversion performance test
[0054] In order to evaluate the photothermal conversion performance of the fabric, a power of 0.5 W / cm 2 The fabric was irradiated with 808nm near-infrared light and detected using an infrared thermal imager to record the surface temperature of the fabric after 5 minutes of irradiation.
[0055] (4) Super hydrophobic high temperature stability test
[0056] In order to evaluate the high temperature stability of the fabric, the fabric was placed in an oven at 120°C for 72 hours and then taken out to measure the change in contact angle.
[0057] (5) Antibacterial test
[0058] In order to study the performance of fabrics under simulated sunlight (2kW / cm 2 ) to inhibit bacterial adhesion and kill bacteria. The original fabric and photothermal superhydrophobic fabric were respectively 6CFU / mL of bacterial suspension was co-cultured for 24 hours and then washed 3 times with PBS buffer. Subsequently, the photothermal superhydrophobic fabric sample was divided into two parts, one of which was irradiated with simulated sunlight for 10 minutes. Then, the above fabric was immersed in 1mL PBS buffer for 5 minutes of ultrasound, and then 20μL of bacterial suspension was spread on a sterile LB agar plate and incubated at 37°C for 18 hours. Finally, the optical photographs of the LB agar plate were recorded and the number of bacterial colonies was calculated. The calculation formula of the antibacterial rate is: Antibacterial rate (%) = [(number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group] × 100%.
[0059]
[0060] Table 1 - Test results of fabric hydrophobicity, high temperature stability and photothermal conversion performance
[0061]
[0062] Table 2 - Test results of antibacterial properties of fabrics
[0063] It can be seen from the performance tests of the embodiments in Table 1 and Table 2 that the super-hydrophobic antibacterial fabrics with photothermal effect prepared in Examples 1-4 have excellent super-hydrophobicity, and still maintain super-hydrophobicity after being treated in a high temperature environment for 72 hours, which can effectively improve the anti-bacterial adhesion of the material. In addition, the fabric has significant photothermal conversion performance, and the photothermal sterilization effect combined with the super-hydrophobic surface makes the antibacterial rate as high as 100%.
[0064] It can be seen from the performance test of the comparative example in Table 1 that the comparative example does not have super-hydrophobicity compared with Example 1. Although the prepared fabric still has excellent light-to-heat conversion performance, and the surface temperature rises to 121°C due to the lack of silica loading, its antibacterial rate against Escherichia coli and Staphylococcus aureus is significantly reduced. The lack of hydrophobic nano-silica in the coating makes it difficult for the fiber to construct sufficient roughness, and the contact angle of the fabric surface is only 142°. Bacteria come into contact with the fabric and are prone to adhesion when cultivated on its surface. Even if simulated sunlight is applied to kill surface bacteria, the small amount of inactivated bacteria attached to it will affect the bactericidal effect, resulting in a decrease in the antibacterial rate of the fabric regardless of whether there is light.
[0065] The super-hydrophobic antibacterial fabric with photothermal effect of the present invention is composed of a photothermal preparation layer, a low surface energy silane coupling agent and hydrophobic nano-silica, and has a chemical cross-linked structure, showing excellent super-hydrophobicity, heat resistance stability, photothermal conversion and photothermal cycle stability. The super-hydrophobicity of the fabric significantly reduces the surface adhesion of bacteria, and the photothermal effect of the fabric synchronously and rapidly kills the attached bacteria, realizing the integrated application of super-hydrophobic antibacterial and photothermal sterilization, with high antibacterial efficiency, wide antibacterial range, long antibacterial life, safe and reliable, and no drug resistance.
[0066] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and modifications can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached requirements.
Claims
1. A method for preparing a super-hydrophobic antibacterial fabric with photothermal effect, characterized in that: The following steps are included: Step S1, surface treating the front and back sides of the fabric with oxygen plasma respectively, then immersing the fabric in a photothermal preparation aqueous dispersion with a volume concentration of 3 to 10 mg / mL for 1 to 3 minutes, then taking the fabric out and drying it in an oven at 60 to 100° C., repeating the immersion and drying 2 to 5 times to obtain a photothermal fabric; Step S2, adding a mixture of 0.5-2 parts of ammonia water and 2-6 parts of water to 95 parts of ethanol by volume, mixing evenly, then adding 0.5-3g of a silane coupling agent with an alkane chain, stirring for 4-12h at a temperature of 25-60°C to obtain a hydrolysis solution, then adding 0.075-0.9g of hydrophobic silica nanoparticles to the hydrolysis solution, and subjecting the solution to ultrasonic treatment for 5-15min to obtain a uniformly dispersed stable modified dispersion; Step S3, placing the photothermal fabric treated in step S1 into the modified dispersion prepared in step S2, stirring at room temperature for 5 to 10 minutes, taking out the photothermal fabric and placing it in an oven at 80 to 120° C. for curing for 0.5 to 4 hours, to obtain a super-hydrophobic antibacterial fabric with a photothermal effect, wherein a silane coupling agent / hydrophobic silica nanoparticle composite coating is attached to the surface of the fabric base of the super-hydrophobic antibacterial fabric, wherein the hydrolyzed silane coupling agent with an alkane chain partially undergoes self-degradation under high temperature conditions of 80 to 120° C. Condensation occurs partially with the hydroxyl or carboxyl groups of the photothermal agent, and partially with the hydroxyl groups between fibers through electrostatic or hydrogen bonding, so that the silane coupling agent / hydrophobic silica nanoparticle composite coating, the fabric base of the superhydrophobic antibacterial fabric and the photothermal agent layer all have good adhesion, and the photothermal agent and hydrophobic nano-silica in the photothermal agent aqueous dispersion are densely accumulated on the fiber surface of the superhydrophobic antibacterial fabric, forming an undulating porous structure formed by a large number of nano-papillae, constructing a uniform micro-nano rough structure.
2. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to claim 1, characterized in that: In step S1, hydrogen bonds or electrostatic interactions between the hydroxyl and carboxyl groups of the photothermal agent and the fabric fibers cause the fiber surface of the fabric to become rough after immersion treatment, thereby increasing the physical adhesion between the photothermal agent and the fiber surface of the fabric and giving the fabric photothermal properties.
3. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to claim 2, characterized in that: In the step S1, the photothermal agent aqueous dispersion is a solution obtained by putting the photothermal agent into water and dispersing it evenly through ultrasonic treatment. The photothermal agent is selected from any one of MXene, carboxylated carbon tubes, and carboxylated carbon black.
4. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to claim 3, characterized in that: In the step S1, the material of the fabric is any one of polypropylene, polyethylene, polyester, polyurethane and cellulose; the type of the fabric is meltblown fabric, non-woven fabric or woven fabric.
5. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to claim 1, characterized in that: In the step S2, the silane coupling agent with an alkane chain undergoes a hydrolysis reaction in ethanol under the promotion of the ammonia water and the water, and the obtained hydrolysis reactant has good compatibility with the hydrophobic silica nanoparticles. After the ultrasonic treatment, the hydrolysis reactant and the hydrophobic silica nanoparticles are uniformly dispersed in the solution and the stable modified dispersion is maintained.
6. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to any one of claims 1 to 5, characterized in that: In the step S2, the silane coupling agent with an alkane chain is selected from at least one of dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane and octadecyltriethoxysilane.
7. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to claim 6, characterized in that: In the step S2, the mass concentration of the silane coupling agent with an alkane chain in the solvent consisting of ethanol, ammonia water and water is 5 to 30 mg / mL.
8. The method for preparing a super-hydrophobic antibacterial fabric with photothermal effect according to claim 7, characterized in that: In the step S2, the particle size of the hydrophobic silica nanoparticles is 20 to 80 nm; and the mass ratio of the hydrophobic silica nanoparticles to the silane coupling agent with an alkane chain is 15 to 30 wt%.
9. A super-hydrophobic antibacterial fabric with photothermal effect, characterized in that: The superhydrophobic antibacterial fabric with photothermal effect is prepared by the preparation method of any one of claims 1 to 8. The superhydrophobic antibacterial fabric with photothermal effect combines passive superhydrophobic antibacterial adhesion and active photothermal sterilization in antibacterial applications, with an antibacterial rate of more than 99.0%, a wide antibacterial range and a long antibacterial life.
Citation Information
Patent Citations
Preparation method of silicon dioxide super-hydrophobic thin film and super-hydrophobic material
CN103359954A
Method for preparing super-hydrophobic flame retardant fabric through one pot method
CN109137467A
Preparation method of super-hydrophobic surface with nanoscale hydrophilic sites
CN113105263A
Super-hydrophobic anti-killing integrated functional surface with shape memory function and preparation method of super-hydrophobic anti-killing integrated functional surface
CN114767949A
Fiber comprising thermoplastic elastomer and silica nanoparticle, stretchable hydrophobic fiber article prepared therewith, and method for preparing the same
US20210062410A1
Cited By
Normal-temperature curing environment-friendly silicon-based nano coating as well as preparation method and application thereof
CN120310429A
Stable photo-thermal anti-icing coating capable of being produced on large scale and preparation method
CN120984543A